2020
DOI: 10.1080/19490976.2020.1766345
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus probiotic prevents airway function deterioration and promotes gut microbiome resilience in a murine asthma model

Abstract: Allergic asthma is a highly prevalent inflammatory disease of the lower airways, clinically characterized by airway hyperreactivity and deterioration of airway function. Immunomodulatory probiotic bacteria are increasingly being explored to prevent asthma development, alone or in combination with other treatments. In this study, wild-type and recombinant probiotic Lactobacillus rhamnosus GR-1 were tested as preventive treatment of experimental allergic asthma in mice. Recombinant L. rhamnosus GR-1 was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 51 publications
(103 reference statements)
1
35
0
Order By: Relevance
“…A beneficial effect of the administration of probiotics was suggested by showing that oral administration of Lactococcus lactis NZ9000 to rats resulted in a decrease in infiltration of pro-inflammatory leucocytes, mainly eosinophils and decreased lung IL-4 and IL-5 expression in the broncho-alveolar lavage and a reduced level of serum allergen-specific IgE [ 24 ]. Another study conducted in mice using Lactobacillus rhamnosus GR-1 significantly prevented airway hyperreactivity development and prevented microbiome disturbance in the asthmatic animals, supporting the existence of the gut–lung axis [ 25 ]. An interesting aspect is that most probiotics are given orally; however, a new approach was tested by giving probiotics ( Lactobacillus paracasei NCC2461 [ 26 ] and Lactobacillus rhamnosus GG [ 27 ] in mice through the nose and showed benefits in reducing inflammation of the lungs [ 28 ].…”
Section: Resultsmentioning
confidence: 95%
“…A beneficial effect of the administration of probiotics was suggested by showing that oral administration of Lactococcus lactis NZ9000 to rats resulted in a decrease in infiltration of pro-inflammatory leucocytes, mainly eosinophils and decreased lung IL-4 and IL-5 expression in the broncho-alveolar lavage and a reduced level of serum allergen-specific IgE [ 24 ]. Another study conducted in mice using Lactobacillus rhamnosus GR-1 significantly prevented airway hyperreactivity development and prevented microbiome disturbance in the asthmatic animals, supporting the existence of the gut–lung axis [ 25 ]. An interesting aspect is that most probiotics are given orally; however, a new approach was tested by giving probiotics ( Lactobacillus paracasei NCC2461 [ 26 ] and Lactobacillus rhamnosus GG [ 27 ] in mice through the nose and showed benefits in reducing inflammation of the lungs [ 28 ].…”
Section: Resultsmentioning
confidence: 95%
“… 16 As such, one potential area for future exploration may be the potential impact of probiotics upon other human diseases for which cough is a predominant feature, including allergic diseases such as asthma; administration of a Lactobacillus rhamnosus resulted in lung protection in a murine allergic respiratory disease model, with the probiotic demonstrated to alter respiratory IL-1β levels, as well as airway total cell counts and lymphocyte counts. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, all activities leading to the maintenance or restoration of the microbiome may represent a new therapeutic approach. Recently it was shown that Lactobacillus rhamnosus GR-1 can alleviate the symptoms in the murine model of allergy ( Spacova et al, 2020 ). In the study, mice were supplemented with 10 10 CFU of bacteria four times per week through 6 weeks.…”
Section: Respiratory Allergy and The Oral Supplementation Of Probioticsmentioning
confidence: 99%